Matrix Model: A Selective Empirical Test - Grimes, A. J.; Klein, Stuart M.; Shull, F. A. (Academy of Management Journal, 1972)
This paper presents the Matrix model of organizational analysis and a partial empirical test of its descriptive validity. The model, concerned with the impact of technology and personal discretion on organization structure, offers a series of propositions about task-unit differentiation and integration. Two major propositions provide the focus of the empirical section of this paper: (1) task units become increasingly autonomous from the administrative system as the structural design moves from the Routine to Heuristic organizational strategy; and (2) task unit members become increasingly autonomous from supervision as the structural design moves from Routine to Heuristic. Data from 828 task units generated from 18 attitude survey items are used to test the first proposition; the data support the proposition, and modifications of the model are suggested.